PEMBERANGKATAN CALON JEMAAH HAJI INDONESIA MELALUI FILIPINA - Zaenal Abidin (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This paper explores the challenges and issues of Hajj handling through the Philippines, the treatment to Indonesian 177 detained pilgrims and the government efforts to resolve the issues. The limited Indonesian hajj quota has caused long waiting lists for enthusiastic pilgrims to perform the fifth pillar of Islam. In some regions, such as South Sulawesi, this waiting list can take up to 40 years. The high enthusiasm of South Sulawesi people has been sought as an opportunity by travel agents to embark the pilgrims through the neighboring country whose quota has not yet fulfilled, e.g. the Philippines. As many as 177 Indonesian pilgrims during the hajj season 1438H/2016 have been processed through the Philippines agency by forging documents. This action resulted in the cancellation of hajj departure and the detention of the pilgrims by the Philippines authority. These pilgrims are detained in the Special Intensive Care Area (SICA) with minimum facilities. Through diplomatic discussion among the Indonesian Embassy in Manila, Ministry of Foreign Affairs, Ministry of Religious Affairs and Indonesian Police Agency, these 177 pilgrims have been released and sent home. KEY WORDS: Hajj Through the Phillipines, Waiting List, Illegal Documents